Benchmarking thermal performance of buildings and identifying preferred thermal conditions with highly deployable IoT devices. Issue 4 (September 2019) - Kokogiannakis, G; Lin, W; Fiorentini, M; Ledo Gomis, L; Cooper, P; Hoskins, E; Elgood, T
Abstract: Low cost, network-based, pervasive sensing devices that capture a range of indoor environmental parameters were successfully developed and deployed in two large mechanically ventilated buildings in Sydney and in Wollongong in Australia. The devices could provide information over the internet for the indoor environment of the buildings at high spatial and temporal resolutions and could also capture occupant expressions of preferences for the indoor thermal environment. The paper describes findings from the monitoring data and the real-time occupant responses that were collected between March/2017 and October/2018. The analysis includes records from approximately 1450 real-time expressions of thermal preferences from the occupants of the two buildings and more than 5.5 million time stamp rows that contained sets of indoor environmental quality data. The paper demonstrates a low-cost method for benchmarking buildings with each other and providing the means of communicating the often-unknown occupant requirements to facility managers.